Facts about Antioxidants - Kaitlin G. Clark; Wendy J. Dahl (EDIS)
Our bodies are made up of cells. Chemical reactions necessary for life are constantly occurring inside our cells, and sometimes they create free radicals — highly reactive molecules that can initiate damaging chain reactions known as oxidative stress. Antioxidants can inactivate free radicals and protect our cells from oxidative stress and the damage it causes. Antioxidants also can help our immune system defend against bacteria, fungi, viruses, and some cancers. The body produces some of its own antioxidants, but eating a plant-based diet increases the level of antioxidants in our bodies. This 3-page fact sheet was written by Kaitlin G. Clark and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, February 2014.